English Teachers’ Challenges in Constructing Remote English Summative Assessment during Covid-19 Pandemic - Nurwahidah Nurwahidah; Maulana Rizki Hamidi; Nida Husna; Muhammad Farkhan; Didin Nuruddin Hidayat; Alek Alek (Linguistic, English Education and Art (LEEA) Journal, 2022)
This study aims to investigate English teachers’ challenges in constructing remote English summative assessments for junior high school students during the COVID-19 Pandemic. The method used in this research is a qualitative method with descriptive research in case study design. The results of this study obtained from 33 English teachers of Junior High schools from 8 big provinces in Indonesia highlighted technical problems and the validity and reliability of the test become the main challenges when the teachers construct a remote summative assessment for junior high school students. Furthermore, the researchers concluded that during the COVID-19 Pandemic, most junior high school teachers face many challenges and can overcome those problems by being tech-savvy teachers. Keywords: COVID-19, English Teacher Challenges, Remote Learning, Summative Assessment